Study on Seismic Performance of a Stiffened Steel Plate Shear Wall with Slits - Jin-yu Lu; Lu-nan Yan; Yi Tang; Heng-hua Wang (Shock and Vibration)
To determine the force mechanism for the steel plate shear wall with slits, the pushover analysis method was used in this study. An estimated equation for the lateral bearing capacity which considered the effect of edge stiffener was proposed. A simplified elastic-plastic analytical model for the stiffened steel slit wall composed of beam elements was presented, where the effects of edge stiffeners were taken into account. The wall-frame analysis model was established, and the geometric parameters were defined. Pushover analysis of two specimens was carried out, and the analysis was validated by comparing the results from the experiment, the shell element model, and a simplified model. The simplified model provided a good prediction of the lateral stiffness and the strength of the steel slit wall, with less than 10% error compared with the experimental results. The mutual effects of the bearing wall and the frame were also predicted correctly. In the end, the seismic performance evaluation of a steel slit wall-frame structure was presented. The results showed that the steel slit wall could prevent the beams and columns from being damaged by an earthquake and that the steel slit wall was an efficient energy dissipation component.